Pseudo-nitzschia species (Bacillariophyceae) identification and delineation using mitochondrial cox1 gene sequences as compared to LSU rDNA - Tan, Suh Nih; Lim, Hong Chang; Teng, Sing Tung; Lim, Po Teen; Leaw, Chui Pin (Springer Verlag (Germany), 2015)
An attempt was made to infer the phylogeny of Pseudo-nitzschia species by using the mitochondrial-encoded gene, cytochrome c oxidase subunit I (cox1), and comparing it with the nuclear-encoded large subunit ribosomal DNA (LSU rDNA). A pair of primers targeting Pseudo-nitzschia cox1 was designed in silico and used to infer the molecular phylogeny of Pseudo-nitzschia. The primer pair was tested using genomic DNAs isolated from six species of Pseudo-nitzschia from Malaysia. The phylogenetic inference of cox1 was then compared to the LSU rDNA phylogeny. Phylogenetic reconstructions of both data sets revealed monophyly of Pseudo-nitzschia species complexes. The range of genetic divergences among Pseudo-nitzschia species were higher in the cox1 data set (3.5–20.4 %) compared to the LSU rDNA data set (0.1–8.8 %). The present study suggests that high genetic divergence in cox1 of Pseudo-nitzschia species could be a useful genetic marker for DNA bar coding.